Penerapan Kriteria Ketuntasan Minimal (KKM) dalam Kurikulum Merdeka : Tantangan dan Solusi di Madrasah - Muhtar Hidayat; Muhammad Ikhsanudin; Kholil Kholil; Ahmad Rosyid Ridha (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The implementation of Minimum Completion Criteria (KKM) in the Independent Curriculum is one of the important problems faced by educational institutions, including madrasas, in efforts to improve the quality of education. KKM is the minimum standard score that must be achieved by students to be declared complete in a subject. In the context of the Independent Curriculum which emphasizes learning based on the potential and uniqueness of students, the implementation of KKM faces several challenges, such as difficulties in more flexible assessments, differences in student ability levels, and limited resources available in madrasas. This study aims to identify the challenges faced by madrasas in implementing KKM and find solutions that can be applied to overcome these problems. The results of the study indicate that the main challenges include a lack of understanding of the implementation of KKM in line with the principles of the Independent Curriculum, as well as difficulties in compiling fair and appropriate assessments. Several proposed solutions include training for educators, developing a more inclusive assessment system, and increasing cooperation between madrasas and other educational institutions. With the implementation of these solutions, it is hoped that KKM can be implemented more effectively, so that it can support the success of the Independent Curriculum in madrasas.